Robotic Hair Transplantation Surgery - Khondoker, MS; Awwal, R; Islam, KMS; Rabbi, RE (Bangladesh Journal of Plastic Surgery, 2010)
Background: Hair transplantation is one of the most evolving procedures in aesthetic surgery accompanied by regular improvement in technique. The recent advancement in technology and the concept of using follicular unit grafts have made this procedure reach a new height. A precise appreciation of anatomy has allowed the use of follicular unit graft. With better methods of harvesting and implantation, hair transplantation results represent a blend of art and science. Materials & method: 60 patients underwent hair transplant surgery from July/2008 to June/2009. Age limit was 18-58 years. Patients were evaluated and prepared in standard way. Operations were done by Robotic follicular unit graft by a specially designed machine. Procedures were performed under nerve block and local infiltration .Grafting sessions lasted for 5-6 hours, during which 1500-2000 FUGs were transplanted. Patients were discharged on the same day. Results: Minimum complications were observed. Most of the patients were satisfied except a few. Some patients needed second sitting surgery. Conclusion: With better methods of harvesting and implantation, Hair transplantation, if done judiciously, is a very rewarding procedure, both for the surgeon and the patient. DOI: http://dx.doi.org/10.3329/bdjps.v1i1.6488 Bangladesh Journal of Plastic Surgery (2010) Vol. 1 (1) pp.19-23